Analisis Faktor - Faktor Hambatan Agent dalam Pembuatan Dokumen Port Clearance dan PHQC Karantina yang di Ageni Oleh PT. ITL Shipping Agency - insani, risky akbar; Siska, Syafni Yelvi (Politeknik Pelayaran Sumatera Barat, 2025)
This study seeks to examine the factors impeding agents in the preparation of Port Clearance and Port Health Quarantine Certificate (PHQC) documents at PT. ITL Shipping Agency. A qualitative case study methodology was utilized, incorporating observation, interviews, and document analysis. The results identify two primary categories of obstacles: internal and external. Internal challenges encompass limited technical proficiency in document preparation and verification, insufficient command of maritime English, and inadequate digital literacy in operating information technology systems. External impediments include substandard office facilities, lack of essential equipment such as laptops, printers, and modems, unstable internet connectivity, expired vessel certificates, unpredictable cargo handling schedules, and adverse weather conditions. These factors contribute to delays in document issuance, diminished operational efficiency, and potential administrative risks for the company. To address these issues, the study advocates capacity building through regular training programs, provision of standardized and modern work equipment, optimization of internet access, and implementation of a cloud-based digital document management system. Through these strategic interventions, agents are anticipated to perform with greater professionalism, accuracy, and efficiency, thereby improving the quality and competitiveness of shipping agency services in the international domain.